Rapid Synthesis of Multifunctional Apatite via the Laser-Induced Hydrothermal Process - Song, Sangmin; Um, Seung-Hoon; Park, Jaeho; Ha, Inho; Lee, Jaehong; Kim, Seongchan; Lee, Hyojin; Cheon, Cheol-Hong; Ko, Seung Hwan; Kim, Yu-Chan; Jeon, Hojeong (American Chemical Society, 2022)
Synthetic biomaterials are used to overcome the limited quantity of human-derived biomaterials and to impart additional biofunctionality. Although numerous synthetic processes have been developed using various phases and methods, currently commonly used processes have some issues, such as a long process time and difficulties with extensive size control and high-concentration metal ion substitution to achieve additional functionality. Herein, we introduce a rapid synthesis method using a laser-induced hydrothermal process. Based on the thermal interaction between the laser pulses and titanium, which was used as a thermal reservoir, hydroxyapatite particles ranging from nanometer to micrometer scale could be synthesized in seconds. Further, this method enabled selective metal ion substitution into the apatite matrix with a controllable concentration. We calculated the maximum temperature achieved by laser irradiation at the surface of the thermal reservoir based on the validation of three simplification assumptions. Subsequent linear regression analysis showed that laser-induced hydrothermal synthesis follows an Arrhenius chemical reaction. Hydroxyapatite and mg2+-, Sr2+-, and Zn2+-substituted apatite powders promoted bone cell attachment and proliferation ability due to ion release from the hydroxyapatite and the selective ion-substituted apatite powders, which had a low crystallinity and relatively high solubility. Laser-induced hydrothermal synthesis is expected to become a powerful ceramic material synthesis technology.